2020
DOI: 10.1038/s41598-020-65067-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vitamin D system in skeletal muscle and resident myogenic stem cell during development, maturation, and ageing

Abstract: Skeletal muscle exhibits enormous plasticity throughout life, however, less is known regarding how the stages of growth regulate its local vitamin D system. Herein, we investigated serum 25(OH)D 3 and ca 2+ levels along with the vitamin D system in skeletal muscle and resident myogenic stem cells of male C57BL/6 mice during development, maturation, and ageing. Compared with development, significant increases in vitamin D receptor (VDR) protein expression in mature and aged muscles were associated with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Moreover, the cooperative action of vitamin D 3 and GCs in modulating gene expression was presented [ 17 ] which implies the potential reduction of the adverse effects of GC excess (during vitamin D 3 supplementation) [ 52 ]. In our study, this phenomenon is partly confirmed because SOL muscle consists of predominantly slow-oxidative fibers, with a larger pool of mitochondria, and EDL is mainly formed of fast-glycolytic muscle fibers [ 53 ]. Our results show that in DEX-induced atrophy rats, SOL muscle is sparing in both absolute ( Figure 5 A) and relative values ( Figure 6 A).…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, the cooperative action of vitamin D 3 and GCs in modulating gene expression was presented [ 17 ] which implies the potential reduction of the adverse effects of GC excess (during vitamin D 3 supplementation) [ 52 ]. In our study, this phenomenon is partly confirmed because SOL muscle consists of predominantly slow-oxidative fibers, with a larger pool of mitochondria, and EDL is mainly formed of fast-glycolytic muscle fibers [ 53 ]. Our results show that in DEX-induced atrophy rats, SOL muscle is sparing in both absolute ( Figure 5 A) and relative values ( Figure 6 A).…”
Section: Discussionsupporting
confidence: 60%
“…In skeletal muscle of mature and aged mice, protein expression of VDR is closely associated with serum concentration of 25(OH)D (Srikuea et al, 2020). The VDR and vitamin D-activating enzyme CYP27B1 are lowly expressed in homeostatic skeletal muscle in vitro and in vivo, evidenced by immunocytochemical and immunohistochemical visualization and immunoblotting in both C2C12 myoblasts and whole mouse muscle (Srikuea et al, 2012(Srikuea et al, , 2020. After muscle injury, the minimal expression of VDR and CYP27B1 observed in homeostatic conditions is starkly augmented.…”
Section: Skeletal Muscle Damage and Regeneration Throughout The Lifespanmentioning
confidence: 99%
“…In mice, VDR protein expression is increasingly elevated from development through maturation and aging (Srikuea et al, 2020); however, a study in human muscle showed an inverse relationship between skeletal muscle VDR expression and age (Bischoff-Ferrari et al, 2004). VDR expression is strongly associated with changes in circulating 25(OH)D concentrations following vitamin D 3 supplementation in older women with vitamin D insufficiency (25OHD of 46.3 ± 9.5 nmol/L; Ceglia et al, 2013).…”
Section: Skeletal Muscle Damage and Regeneration Throughout The Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several studies have shown a link between periodontal disease and some frequent systemic pathologies [ 10 ] such as diabetes [ 11 ], cardiovascular disease [ 12 , 13 ], respiratory disease [ 14 ], obesity [ 15 ], cancer [ 16 , 17 ], and preterm birth (PTB) [ 7 ]. Vitamin D is a secosteroid that can be ascribed to steroid hormones if considering its biological effects on several tissues [ 18 , 19 , 20 , 21 , 22 ]. Vitamin D might affect periodontal disease both through an effect on bone mineral density and through immunomodulatory effects [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%